Influence of microwave vacuum drying on the effective moisture diffusivity of seedless white grapes - LEI,Yongdong (2022)
Abstract In this study, the effects of microwave power, vacuum degree and load weight on the moisture content of seedless white grapes (Vitis vinifera L.) during microwave vacuum drying were investigated. The result found that during microwave vacuum drying, the effective moisture diffusivity (Deff) of seedless white grapes ranged between 1.0232 × 10−9 and 4.6354 × 10−9 m2/s. The Deff values increased with the increase in the microwave power and the decrease in the load weight, the vacuum degree played a relatively minor role. The kinetics of moisture ratio and drying time were established, with the drying process following the Page model, as reflected by the fitting between model-predicted and measured data. The Page model was demonstrated to precisely describe and predict the moisture content variation in seedless white grapes during microwave vacuum drying.